2019
DOI: 10.1002/smll.201902642
|View full text |Cite
|
Sign up to set email alerts
|

Facile Nanolization Strategy for TherapeuticGanoderma Lucidum Spore Oilto Achieve Enhanced Protection against Radiation‐Induced Heart Disease

Abstract: Radiotherapy (RT) has been extensively utilized for clinical cancer therapy, however, excessive generation of reactive oxygen species (ROS) is becoming a main cause for radiation‐induced heart disease (RIHD). Ganoderma lucidum spore oil (GLSO) is a popular functional food composite with potent antioxidant activity, but it is compromised by poor solubility and stability for further application. Therefore, a strategy for rational fabrication of GLSO@P188/PEG400 nanosystem (NS) is demonstrated in this study to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…As a traditional Chinese medicine, Ganoderma lucidum is often applied in remedying cardiovascular and cerebrovascular ailments (Xie et al, ), especially in the myocardial protection, enhancement of myocardial function, and improvement of cardiovascular blood circulation (Dai, He, Ma, & Chen, ; Sudheesh, Ajith, & Janardhanan, ). Ganoderic Acid A (GAA), a sort of triterpene substance, is the paramount compound of G .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a traditional Chinese medicine, Ganoderma lucidum is often applied in remedying cardiovascular and cerebrovascular ailments (Xie et al, ), especially in the myocardial protection, enhancement of myocardial function, and improvement of cardiovascular blood circulation (Dai, He, Ma, & Chen, ; Sudheesh, Ajith, & Janardhanan, ). Ganoderic Acid A (GAA), a sort of triterpene substance, is the paramount compound of G .…”
Section: Introductionmentioning
confidence: 99%
“…of myocardial function, and improvement of cardiovascular blood circulation (Dai, He, Ma, & Chen, 2019;Sudheesh, Ajith, & Janardhanan, 2013). Ganoderic Acid A (GAA), a sort of triterpene substance, is the paramount compound of G. lucidum (Cao et al, 2017).…”
mentioning
confidence: 99%
“…In a previous review, we introduced many nanoradioprotectors. Thereafter, new nanoradioprotectors, such as ultrasmall Au‐MoS 2 clusters, [ 177 ] PVP‐coated PtPdMo nanocubes, [ 178 ] PtPd nanocrystals, [ 179 ] naturally derived PHA‐L protein NPs, [ 180 ] CeO 2 /Mn 3 O 4 nanocrystals, [ 57 ] pH‐triggered Mn clusters, [ 181 ] polydopamine@arginine–chitosan (thalidomide) nanodrugs, [ 58 ] Nb 2 C‐PVP nanosheets, [ 31 ] CNSI, [ 32 ] and the GLSO@P188/PEG400 nanosystem, [ 37 ] have emerged. Their emergence enriched the treatment pattern in the radioprotection field.…”
Section: Discussionmentioning
confidence: 99%
“…recently described the nanolization of ganoderma lucidum spore oil (GLSO) to improve protection against radiation‐caused heart disease ( Figure ). [ 37 ] GLSO, a popular functional natural food composite that is mainly obtained from Ganoderma lucidum (leyss. ex.…”
Section: Nanomaterials Design For Prevention and Treatment Of Various mentioning
confidence: 99%
“…Polysaccharides are hydrophilic [40], hence abundant in decoctions, whereas triterpenes are not [33]. In fact, Dai et al [34] suggested that G. lucidum spore oil, which although it can be useful as a radioprotector, has the drawback of poor water solubility, which remains a major obstacle for their further development and clinical application in human health care. For this reason, these authors developed a GLSO@P188/PEG400 nanosystem (NS) to improve the efficiency of the radioprotective treatment, especially when this system has functional food composites with hydrophobic defects, such as triterpenes, but not polysaccharides.…”
Section: Discussionmentioning
confidence: 99%